2015
DOI: 10.1039/c5ra18723k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a novel dendrimer core of oxo-vanadium phthalocyanine magnetic nano particles: as an efficient catalyst for the synthesis of 3,4-dihydropyrano[c]chromenes derivatives under green condition

Abstract: A novel magnetically recoverable nanocatalyst with an amino vanadium oxo phthalocyanine pending, was synthesized, characterized and applied for the preparation of 3,4-dihydropyrano[c]chromenes derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Shahrisa et al reported the synthesis of N-sulfonylformamidines (149) using an N-heterocyclic complex-copper complex supported on magnetic cellulose (NHC-Cu@MCs) from the three-component reaction among arylsulfonyl azide (148), secondary alicyclic amines (108c) such as morpholine, Nmethylpiperazine, piperidine and pyrrolidine, and triethylamine (117f) in acetonitrile at rt in 85-94% yield (Scheme 63). 133 The NCs were synthesized via the treatment of ionic liquid-graed magnetic cellulose with copper iodide, potassium tertbutoxide in THF, and further well characterized via TGA, VSM, SEM, XRD, EDX, and FT-IR.…”
Section: Cunp-catalyzed Synthesis Of Heterocyclesmentioning
confidence: 99%
“…Shahrisa et al reported the synthesis of N-sulfonylformamidines (149) using an N-heterocyclic complex-copper complex supported on magnetic cellulose (NHC-Cu@MCs) from the three-component reaction among arylsulfonyl azide (148), secondary alicyclic amines (108c) such as morpholine, Nmethylpiperazine, piperidine and pyrrolidine, and triethylamine (117f) in acetonitrile at rt in 85-94% yield (Scheme 63). 133 The NCs were synthesized via the treatment of ionic liquid-graed magnetic cellulose with copper iodide, potassium tertbutoxide in THF, and further well characterized via TGA, VSM, SEM, XRD, EDX, and FT-IR.…”
Section: Cunp-catalyzed Synthesis Of Heterocyclesmentioning
confidence: 99%
“…Also, these compounds are significant in organic chemistry because of their unique and useful biological activity. [5][6][7][8][9][10][11][12][13][14] Too many methods for the synthesis of 2-amino-4Hchromene derivatives using one-pot Knoevenagel condensation of aldehydes, 1,3-dicarbonyles, and malononitrile in the presence of many catalysis such as [Sipim]HSO 4, [15] CuO nanoparticles, [16] nano Al 2 O 3, [17] DAHP, [18] TBBDA, [19] SDS, [20] MNP@AVOPc [21] and POPINO. [22] However, some of these methods have limitation and disadvantages such as: high cost, high reaction temperature, low yields, and long reaction times, use of toxic solvents, poor recovery and reusability of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our efforts to synthesize of novel catalysts and MCRs, we wish to report the synthesis of novel nano molten salt tetra‐2,3‐pyridiniumporphyrazinato cobalt tribromomethanide [Co (TPPABr)]CBr 3 as an efficient catalyst (Scheme ) for the synthesis of henna‐based compounds under various conditions (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29][30] Phthalocyanines have found a varied range of application in the area of material science due to their distinct optical and electrical properties as well as their thermal stability. [31][32][33][34][35] In continuation of our efforts to synthesize of novel catalysts and MCRs, [36][37][38] we wish to report the synthesis of novel nano molten salt tetra-2,3-pyridiniumporphyrazinato cobalt tribromomethanide [Co (TPPABr)]CBr 3 as an efficient catalyst (Scheme 1) for the synthesis of henna-based compounds under various conditions (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%